Occupational Health and Safety in the Healthcare Sector - Modenese, Alberto; Gobba, Fabriziomaria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Healthcare workers are exposed to several different occupational risk factors, and they pay an important tribute in terms of occupational diseases and work-related injuries. Currently, the COVID-19 pandemic has focused the attention on the problem of the infectious risk, which is certainly among the risks typically expected and specifically recognized for the health personnel, but also other occupational risks should not be overlooked, such as, e.g., the risks associated with work-organization factors and with the exposure to chemical and physical agents. The health consequences associated with the exposure to all these factors have relevant impacts in terms of induced diseases, DALYs, sickness absence from work and costs for the health systems. According to these premises, this reprint has collected manuscripts addressing topics related to the prevention of the occupational risks in the healthcare sector, including original articles and reviews on the prevention of work-related illnesses and injuries of the health personnel, as well as on the evaluation of the risks in the healthcare workplaces, and on the topics of risk perception and of the knowledge and attitudes of the workers towards the preventive procedures and the use of protections. The themes of the prevention of occupational infectious risk, biomechanical overload of the musculoskeletal system and work-related psychosocial factors are specifically discussed in the papers collected.